Segregación por gravedad en aleaciones aluminio-uranio - Balzaretti, D. E.; Biloni, Heraldo (Comisión Nacional de Energía Atómica; Argentina, 1972)
Fil: Balzaretti, D. E. Comisión Nacional de Energía Atómica; Argentina